If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -236 = 76 + 18x Reorder the terms: -236 + 12x = 76 + 18x Solving -236 + 12x = 76 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. -236 + 12x + -18x = 76 + 18x + -18x Combine like terms: 12x + -18x = -6x -236 + -6x = 76 + 18x + -18x Combine like terms: 18x + -18x = 0 -236 + -6x = 76 + 0 -236 + -6x = 76 Add '236' to each side of the equation. -236 + 236 + -6x = 76 + 236 Combine like terms: -236 + 236 = 0 0 + -6x = 76 + 236 -6x = 76 + 236 Combine like terms: 76 + 236 = 312 -6x = 312 Divide each side by '-6'. x = -52 Simplifying x = -52
| 3.4=400a+20b | | 2/5h-16=3/5h-14 | | t=7-10(39-1) | | -6x+7(-3x-34)=32 | | t=-6+4(15-1) | | 4x^2+x=-4 | | t=19+6(52-1) | | 0=8x^2+8x+1 | | 115-1/6 | | 251-17x=-9x-285 | | t=-38-7(52-1) | | -25.5=9(8.5x-6) | | 425=(2h-10)+h | | 4n^2+7n-9=0 | | -18x+50=-22x-126 | | 9y+3x=54 | | -164+2x=363-15x | | 115=x*1.633 | | 115=x*1.63 | | -6x+6(6x-12)=-282 | | 115=x*1.6 | | 115=x*1.6335227 | | 83-24x=-18x-253 | | -24-27x=-26x+23 | | -24-27x=-26+23 | | 26.5=-8.5n-9.5n | | 528=-12(-7x+33) | | 2.3x+4.2y=10.8 | | (x^2+2x*y)dx+x*y*dy=0 | | 660=-10(8x+38) | | sqrt(5x+1)-sqrt(3x-5)=2 | | 3x+4w=13 |